2021
DOI: 10.1080/17482631.2021.1939937
|View full text |Cite
|
Sign up to set email alerts
|

The birthing room and its influence on the promotion of a normal physiological childbirth - a qualitative interview study with midwives in Sweden

Abstract: The birthing room is a major workplace for midwives but how it influences them in practice is not enough investigated. Purpose: This study aimed to explore midwives´ experiences of how the birthing room affects them in their work to promote a normal physiological birth. Methods: A phenomenological reflective lifeworld research approach was used and included individual interviews with 15 midwives working at four different hospitals in western Sweden, and of which two also assisted at homebirths. The analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Earlier research in the R4B project showed that the birthing room design can either contribute to or prevent midwives from supporting a healthy and normal physiological birth. The midwife must be present, make the room private and homey, and support the mother to be active and protect her from disturbing elements both inside and outside the room ( Andrén et al, 2021 ). Yet, another R4B study identified that the birth environment consists of the physical birthing room, the human encounter within it, and the institutional context where women give birth.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research in the R4B project showed that the birthing room design can either contribute to or prevent midwives from supporting a healthy and normal physiological birth. The midwife must be present, make the room private and homey, and support the mother to be active and protect her from disturbing elements both inside and outside the room ( Andrén et al, 2021 ). Yet, another R4B study identified that the birth environment consists of the physical birthing room, the human encounter within it, and the institutional context where women give birth.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the new room had no effect on the CEQ2 subdomain professional support, which indicates that the provided care did not differ between the two groups. Previous research has provided knowledge of how the physical design has the potential of enabling healthcare providers to support women during physiological birth (Andrén et al, 2021). In one of our earlier studies, we have described how a room that conveys a sense of comfort, familiarity, and integrity has the potential to symbolize tenderness and care for birthing women in an otherwise unfamiliar hospital context (Goldkuhl, Dellenborg et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a midwifery model of woman-centered childbirth care, developed in studies in Sweden and Iceland, one of the three central and intervening themes in the model is to create “a birthing atmosphere” that fosters feelings of calm, trust, and safety and that supports a sense of normalcy. The midwife has a central role in creating such a birthing atmosphere, but in a hospital-based birth environment, this is a great challenge (Berg et al, 2012) due to the dominance of a medico–technical perspective both in guidelines and in the presence and extensive use of medico–technical equipment (Andrén et al, 2021; Davis & Homer, 2016). For midwives, it is therefore a major challenge to create a positive space for childbirth (Andrén et al, 2021; Berg et al, 2012; Davis & Homer, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the Swedish Room4Birth research project, we found that the birthing room, through its design, could support either a salutogenic physiological birth process or a pathological treatment of childbirth (Andrén et al, 2021; Goldkuhl et al, 2022). We also found that birthing rooms adaptable to the needs of the birthing women helped them feel welcomed and supported, resulting in a more positive birth mood (Skogström et al, 2022), and that women cared for in more personally adapted rooms expressed a greater sense of safety, control, and integrity than did women being cared for in regular birthing rooms (Goldkuhl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%